An ancient cranium from Dmanisi: Evidence for interpersonal violence, disease, and possible predation by carnivores on Early Pleistocene Homo. Issue 166 (May 2022) - Margvelashvili, Ann; Tappen, Martha; Rightmire, G. Philip; Tsikaridze, Nikoloz; Lordkipanidze, David
Abstract: Five well-preserved individuals from Dmanisi represent a paleodeme attributed to early Homo . Here we provide a case study of the D2280 adult cranium, which presents four oval-shaped lesions on the frontal, left parietal, and occipital bones. Several conditions are considered as possibly contributing to this pathology, including trauma, cysts, metastatic cancer, and infectious disease. One large but shallow depression on the left parietal bone has slightly elevated boundaries. Imaging reveals inner and outer tables that are reciprocally concave, so that the diploë is diminished or completely absent. This lesion is very likely a result of traumatic injury. Two additional depressions on the left side frontal and occipital bones may also be attributed to blunt force trauma. Such injuries stem from a variety of causes, but interpersonal violence may well be implicated. Based on the location and structure of a fourth lesion on the right-side frontal bone, we advance a possible diagnosis of treponemal disease. Lesions on the cranium and specifically on the frontal bone are common in treponemal disease. The condition develops as a periostitis, which eventually results in the destruction of the osteoperiosteal border of the cranial outer table and rarely involves the inner table. Additional perforations on the occipital bone are interpreted as perimortem damage resulting from predation by carnivores or scavenging by birds. If our reading of this cranial evidence can be confirmed, then D2280 documents one of the earliest instances of blunt force trauma in the Homo lineage. Dmanisi may also reveal the presence of treponemal disease in a population dated ca. 1.77 Ma ago. These findings bear on the social behavior of ancient humans and also the impact of infectious diseases on their survival.